E-Governance Implementation in the Education System: A Comparative Study in Bangladesh and Indonesia - Md. Hasan; Md. Sajal Miah; Hasibur Rahman; Parvez Simol; Md Saber Hossen; Abdullah Abdullah; Mohammad Shaheen Alam; Tahamina Akter; Rajib Das (Transpublika Publisher, 2026)
The rapid advancement of ICT has transformed education governance worldwide. E-governance in education has emerged as an important tool for improving administrative efficiency, transparency, accessibility, and service delivery in developing countries. This study compares Bangladesh and Indonesian education e-governance experiences on institutional preparation, digital literacy, and stakeholder satisfaction. Digital media is being used more in education in both countries to boost efficiency. This report compares education system e-governance implementation in those nations. The goal is to analyze governance and compare the obstacles both countries confront in adopting and implementing e-government in education. This mixed-methods comparative case study analyses Bangladesh and Indonesia as parallel units. This architecture allows systematic evaluation of each country’s e-government framework, digital infrastructure, and educational service delivery. The study uses only secondary data. The results showed that both countries struggle to adopt education e-governance. Bangladesh has weak infrastructure and little digital literacy, while Indonesia has stronger technology but regional differences and remote area opposition to digital transformation. This research has several practical implications for policymakers, educators, and stakeholders. The study reveals to policymakers the necessity of strategic planning, investment in digital infrastructure, and inclusive policies. These papers can also serve as a reference for enhancing digital governance in the education sector and eliminating the urban-rural digital gap. This paper recommends that it is extremely essential to overcome infrastructure issues and promote cost-effective technologies. So that they share some common issues, yet e-governance can help open up the education system, making it more accessible and efficient.